Immersive Chemistry Learning with Augmented Reality: Exploring Students’ Needs on Visualizing Chemical Bonding - Setiawan, Riky; Santosa, Eka Budhi; Sukmawati, Fatma (Indonesian Journal of Instructional Media and Model, 2025)
The digital transformation of education has opened broad opportunities for innovation, yet the use of advanced technologies such as Augmented Reality (AR) in chemistry learning remains limited, particularly in Indonesia. The present research examines high school students’ needs for AR-based instructional media on the abstract topic of chemical bonding. A descriptive quantitative approach was employed within the Analysis phase of the ADDIE instructional design model. Data were collected using a validated questionnaire administered to 51 eleventh-grade students from a senior high school in Surakarta, Indonesia. The results show that more than 84% of students experience difficulties in learning chemistry, with chemical bonding identified as the most challenging topic (88.2%), mainly due to limited visualization and the abstract nature of the content. Students also perceived the instructional media currently used in class as insufficiently engaging and not yet effective in helping them understand chemical bonding. Although 90.2% of students had never used AR in chemistry lessons, nearly 59% expressed strong interest in its implementation. This study offers an empirical mapping of students’ cognitive, media-related, and technological needs as a foundation for designing AR-based chemistry learning on chemical bonding. As far as we are aware, it is one of the first studies in the Indonesian context to conduct a structured needs analysis for AR integration specifically on chemical bonding within the ADDIE framework. At a practical level, the findings provide guidance for instructional designers and chemistry teachers regarding the urgency of developing immersive AR tools that bridge abstract chemical representations with spatial visualization while also enhancing student engagement in the digital era.